Heavy Metal Concentrations in Roadside Soils on the Białystok-Budzisko Route in Northeastern Poland - Mirosław Skorbiłowicz (MDPI AG, 2021)
Civilization development has contributed to environmental pollution. In recent years, the number of vehicles has increased significantly; according to the Central Statistical Office, the number of passenger cars in Poland in 2000 was nearly 10 million, while in 2020 it was slightly more than 25 million. The study aimed to determine the content and spatial distribution of trace elements (Fe, Mn, Cd, Pb, Cr, Ni, Zn and Cu) in the roadside topsoil along the trunk road Białystok–Budzisko on different types of land use (urban, rural, agricultural and forestal areas). Forty-five soil samples were collected from a 160 km road section, at intervals of approximately 4 km. Metal contents were analyzed by atomic absorption spectrometry. The concentrations of metals in roadside soils occurred in the following order: Fe > Mn > Zn > Cr > Cu > Pb > Ni > Cd. The average contents of Cd, Zn, Cu, and Pb were higher than the geochemical background values of the Polish soils. Moreover, the values of the Igeo showed for Cd moderate to strong, while for Zn, Cu and Pb, moderate soil contamination. The study indicates that significant metal-binding factors in the studied roadside soils are Fe and Mn oxides. The crucial source of metals is road transport, depending on its intensity, which means amount, type, and speed of vehicles. Moreover, based on the analysis of the course of the factor values and their dynamics, it was observed that the areas where typical activities connected with the population take place (urban and agricultural areas) are additional sources of heavy metals. The results of this paper are relevant to the prevention and control of heavy metal pollution in roadside soils. The study can contribute to reducing the concentration of toxic elements in ecosystems due to vehicle emissions with appropriate land-use policies.